Production of activated carbon from coal with H3PO4 activation for adsorption of Fe(II) and Mn(II) in acid mine drainage - Suliestyah, Suliestyah; Tuheteru, Edy Jamal; Yulianti, Ririn; Palit, Christin; Yomaki, Caroline Claudia; Ahmad, Shahrul Nizam (Brawijaya University, 2024)
Acid Mine Drainage (AMD) contains Fe(II) and Mn(II) metals, which can cause environmental pollution. This research aimed to investigate the potency of activated carbon made from coal as an adsorbent in AMD treatment. The carbon was made of coal and activated with H3PO4 in a weight ratio of 40%, 800 °C for 120 minutes while supplying 1.5 L/min of nitrogen during the carbonization process. The result shows that BET surface area, total pore volume, and iodine number were 296.4 m2/g, 0.156 cc/g, and 1205 mg/g, respectively. The surface contained many fractures, channels, and big holes, as evidenced by the FT-IR and SEM investigations, and it also had acidic surface functional groups. The optimum contact time adsorption for AMD treatment was 30 minutes, and the first concentration of Fe(II) and Mn(II) metals affected the adsorption. The optimum removal of Fe(II) in AMD treatment was 95.27% at an initial concentration of 3.51 ppm, while the optimum removal of Mn(II) was 99.82% at an initial concentration of 5.71 ppm. This activated carbon has a considerable potency to be used as the adsorbent in AMD treatment to reduce Fe(II) and Mn(II) levels.